MEET NITE LIVE NEWS ANALYSIS ON NEWS COMPLETENESS VIA TIKTOK SOCIAL MEDIA - Muhammad Galuh Natawinata,; Arvin Hardian,; Muhamad Khadafi Firman, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The increasingly rapid development of information technology has encouraged media outlets to adapt their news presentation. One way to do this is through the use of TikTok, which now serves not only as entertainment but also as a means of information. The Meet Nite Live news program broadcast by Metro TV was also uploaded via the official @MetroTV account on TikTok in short video format. This study aims to analyze the completeness of the news based on the 5W+1H elements and assess the effectiveness of information delivery via TikTok. The news delivered is based on gatekeepimg, agenda setting and journalism theory regarding news completeness. The research method used was descriptive qualitative and constructive paradgm, with data collection through observation and documentation of Meet Nite Live video content from April to June 2025. The results showed that most of the news presented met the 5W+1H elements, although some news items were incomplete in their information delivery. In general, the short video format on TikTok has proven effective in attracting audience attention, making Meet Nite Live a potential alternative medium for information delivery in the digital age.